Family members' perspectives on learning cognitively unimpaired older adults' amyloid‐β PET scan results. Issue 11 (12th July 2021) - Largent, Emily A.; Abera, Maramawit; Harkins, Kristin; Feldman, Sara J.; Uhlmann, Wendy R.; Roberts, J. Scott; Karlawish, Jason; ,
Abstract: Background/Objectives: Disclosure of Alzheimer's disease (AD) risk information to cognitively unimpaired older adults may become more common if preclinical AD is shown to be identifiable and amenable to treatment. Little, however, is known about how families will react to this information. Design and Setting: Semi‐structured telephonic interviews. Participants: Seventy study partners (mean age = 68 [±11]; 50% female; 70% spouses/significant others; 18% children, siblings; 12% friends) of cognitively unimpaired adults who learned a personalized AD dementia risk estimate and an amyloid‐β PET scan result through their participation in preclinical AD research. Measurement: Interviewees were asked about their desire for information regarding their family member's AD dementia risk, baseline expectations of risk, understanding of amyloid‐β PET scan results, and the impact of AD dementia risk information on emotions, health behaviors, and future plans, as well as on perceptions of their family member's or friend's memory. Results: Interviewees generally understood the AD dementia risk information (83%) and considered it valuable (75%). Risk information perceived as favorable elicited feelings of happiness and relief; unfavorable information elicited disappointment, as well as increased awareness of the participants' memory and monitoring for incipient changes in cognition. While noting that AD dementia risk information was not medically actionable at this time due to the lack of disease‐modifying therapies, some interviewees described changes to their family members' and their own health behaviors and future plans. Conclusion: Guidelines for the disclosure of AD dementia risk estimates and biomarker results to cognitively unimpaired adults should account for the needs and interests of individuals and their family members, who may step into a pre‐caregiver role.